"Do We Have LIFT-Off?" Social Media Marketing and Digital Performance at a British Arts Festival. - Miles, Sam (Journal of Arts Management, Law & Society, 2018)
Arts festivals have been explored through many lenses, but social media marketing and digital performance are less studied. The potential of social media networks in digital performance is exemplified by the London International Festival of Theatre (LIFT), which repositions social media technology as an enabler for audiences to co-produce digitally oriented performance. This article argues that the relationship between social media marketing and performance is more hybridized than often assumed, with performances forming a creative development loop from producer to audience through performative social media. Harnessing the creative potential of social media platforms via "digital staging" encourages audience insight into process as well as product.